Antidiabetic and lipid-lowering therapy modify the association between triglyceride–glucose index and acute kidney injury in critically ill patients with coronary artery disease - Yang, Yuehang; He, Linfeng; Jiao, Xueying; Luo, Hanshen; Qiu, Xiang; Shi, Chuli; Ding, Li; Shi, Jiawei (Frontiers in Endocrinology, 2025)
BackgroundAcute kidney injury (AKI) is a common and serious complication in critically ill coronary artery disease (CAD) patients. The triglyceride-glucose (TyG) index, a surrogate marker of insulin resistance, has been linked to adverse cardiovascular and renal outcomes. However, whether antidiabetic drugs or lipid-lowering drugs modify its association with AKI in this population remains unclear.MethodsThis study retrospectively analyzed 2,517 critically ill CAD patients from the MIMIC-IV database. Patients were stratified according to the use of antidiabetic and lipid-lowering drugs. The primary endpoint was the occurrence of AKI during hospitalization. Multivariable logistic regression and restricted cubic spline (RCS) models were applied to examine the association between the TyG index and AKI risk. Subgroup analyses, sensitivity analyses, and independent external validation were performed to assess the robustness of the findings.ResultsThe median age of patients was 69 years, and 68.06% were male. In the fully adjusted logistic regression model, a higher TyG index was significantly associated with an increased risk of AKI among patients without the use of antidiabetic drugs (OR 2.021, 95% CI 1.674–2.454) or lipid-lowering drugs (OR 1.912, 95% CI 1.648–2.228). With the use of antidiabetic drugs, this association remained significant but was attenuated (OR 1.480, 95% CI 1.190–1.853), with a significant interaction observed between the use of antidiabetic drugs and the TyG index in relation to AKI risk (P for interaction = 0.040). With the use of lipid-lowering drugs, the association between the TyG index and AKI risk was weakened (OR 1.445, 95% CI 0.934–2.307), but no significant interaction was found (P for interaction = 0.332). RCS analyses demonstrated a linear relationship between higher TyG index values and increased AKI risk. Similar results were confirmed in external validation.ConclusionsIn critically ill CAD patients, a higher TyG index was independently associated with an increased risk of AKI, whereas this association was attenuated in those with the use of antidiabetic or lipid-lowering drugs. These findings highlight the importance of incorporating metabolic risk assessment into the management of critically ill patients and underscore the potential of pharmacological interventions to improve renal outcomes.